Pengenalan Nilai Estetis Tari Melalui Pembelajaran Seni Budaya dalam Kurikulum Merdeka - Ananda, Rizky; Olga, Evon Natasha; Levin, Cuttri; Sagala, Mastri Dihita (Prodi Pendidikan Sendratasik FKIP UMTAS, 2025)
ABSTRACT This study aims to identify, explain, and demonstrate the aesthetic values found in dance through art and culture learning that adopts differentiated, jigsaw, and cooperative learning methods. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with an art and culture teacher, direct classroom observations, and documentation in the form of student dance performance videos at SMPN 3 Sungai Raya. Data validity was ensured through triangulation of sources, techniques, and time. The data analysis was conducted interactively through the processes of data reduction, presentation, and conclusion drawing. The findings show that the application of these learning methods enabled students to express their understanding of aesthetic values in dance through the creation and performance of original choreographies. The aesthetic values were reflected in the students’ mastery of the elements of movement, rhythm, space, energy, and timing in a harmonious manner. Furthermore, this activity encouraged students to become active participants in the learning process, emphasizing not only technical dance skills but also appreciation for the meaning and expression embedded in cultural contexts. Thus, dance learning contributes to the development of students’ aesthetic awareness and character in alignment with the principles of the Independent Curriculum. These findings imply that a student-centered learning approach that allows for creative expression aligns with the principles of the Merdeka Curriculum in developing students' aesthetic insights and character holistically. Keywords: Aesthetic Value, dance, art and culture learning, independent curriculum